Fostering the lean approach as a sustainable strategy: challenges from portuguese companies - Silva, Angela (2022)
Over the last years the sustainability of current manufacturing processes adopted by industries have been drawn attention worldwide. In response to this challenging, Lean Manufacturing has appeared as an alternative to support companies creating strategies towards sustainable practices. This research aims to evaluate the Lean tools as sustainable strategies implemented in companies located in the North of Portugal. The work was developed mainly based on an online survey applied to 102 Portuguese companies. From the research conducted, results showed that 5S and TPM methods were the tools which have higher progress of implementation by the consulted companies. Regarding the dimension of the consulted companies, results showed that micro and small were the ones with the lowest levels of implementation of lean procedures. The study allowed to suggest some implication regarding key Lean tools adopted by companies operating in the region and a set of barriers faced were also pointed out.